Climate risk and financial stability in Africa: A comparative study before and during the Paris agreement - Joseph Opuni-Frimpong (Sustainable Futures, 2025)
This study examines the impact of climate risk (CRI)11 CRI is Climate risk , AFC is African countries, ZSC is Z-score, BOA is Bank return on Assets , PCP is Private Credit to GDP ratio, CON is Bank concentration, BDP is Bank deposit to GDP, GDP is GDP per capita , GDG is GDP growth, INF is Inflation rate, COC is Control of Corruption, GOE is Government Effectiveness, POS is Political Stability, RGQ is Regulatory Quality, VOA is Voice and Accountability and ROL is Rule of Law on the financial stability of African countries (AFC), measured by their ZScore, before and during the enactment of the Paris Agreement (PAG) and for the period 2010–2019. It also explores the impact of their governance system on the relationship between CRI and financial stability. Data from thirty-two African countries and various regression analyses were estimated for the study. Robust analyses were used to validate the findings. The study found that before, during the enactment of the PAG and for the period 2010–2019, CRI had no impact on the financial stability of AFC. Additionally, their governance system did not impact on the relationship between CRI and financial stability. As AFC face severe challenges, coupled with the fact that CRI exposure had no significant impact on AFC financial stability following the enactment of the PAG, in addition, the fact that their governance mechanisms do not mitigate CRI exposure, highlights the urgent need to integrate climate risk exposure in the financial monitoring system of African countries and the need to address the challenges that AFC face. To the author's knowledge, this study is the first to examine the impact of CRI on the financial stability of AFC considering the enactment of the PAG and how other mechanisms impact their CRI exposure and their financial stability.